S110. Intraoperative neurophysiological monitoring team's communiqué with anesthesia professionals. (May 2018) - Tewari, Anurag; Castle, Joshua; Frye, Tiffany; Taylor, Teal; Schaiper, Lindsy; Mahmoud, Mohamad
Abstract : Introduction: Intraoperative neurophysiological monitoring (IONM) is the standard of care during many spinal, vascular, and intracranial surgeries. High quality perioperative care requires the communication and cooperation of several multidisciplinary teams. One of these multidisciplinary services is intraoperative neuromonitoring (IONM), while other teams represent anesthesia, and surgery. Few studies relate to IONM team's objective communication with the anesthesia providers. We accomplished a retrospective review of IONM related quality assurance data to identify how changes evoked potentials observed during the surgery were communicated within our IONM-anesthesia team and determined the resulting qualitative outcomes. Methods: Quality assurance records of 3112 patients who underwent surgical procedures with IONM (from 2010 to 2015) were reviewed. We examined communications regarding perioperative evoked potential or EEG fluctuations that prompted neurophysiologists to alert/notify anesthesia team to consider alteration of anesthetic depth/drug regimen or patient positioning and analyzed the outcomes of these interventions. Results: Of the 1280 (41.13%) total communications issued, there were 347 notifications and 11 alerts made by neurophysiologist to the anesthesia team for various types of neuro/orthopedic surgeries. Prompt communication led to resolution of 90% of alerts and 80% of notifications after corrective measures were executed by the anesthesiologists. Notifications mainly related to limb mal-positioning and extravasation of intravenous fluid. Conclusion: Based our institutions' protocol and algorithm for intervention during IONM-supported surgeries, our findings of resolution in alerts and notifications indicate that successful communications between the two teams could potentially lead to improved anesthetic care and patient safety.